Smallholder farmers use conservation agriculture-based technologies and sustainable intensification practices adapted to climate change on 627,000 ha in southern Africa - CGIAR Research Program on Maize (2020)
Long-term (2004-2020) Conservation Agriculture (CA) systems research in Malawi, Zambia and Zimbabwe has generated scientific evidence on productivity, profitability, environmental, social and human impacts. This is used in all target countries to inform policies towards more climate-smart agriculture adaptation interventions. Farmer adoption reached >627,000 ha, with yield benefits of 30-50% (up to 140%) under drought. Due to greater water-use efficiency, applying the principles of CA is effective in reducing climate risks thus reducing the vulnerability of farming communities.